Coping Strategies Adopted by Health Professionals during the COVID-19 Pandemic - Couto, Ricardo Neves (2022)
Objective. The objective was to know the coping strategies adopted by health professionals during the COVID-19 pandemic. Method. This was an exploratory research. The participants were 155 health professionals (female 68.2, male 31.8) from northeastern Brazil, mostly from Piauí (39.1%) and Ceará (22.5%), and a mean age of 33.26 years (SD = 7.94). Results. Through a Descending Hierarchical Classification (CHD), the main corpus was divided into two branches: Class 1: Socio-emotional support and spirituality, and Class 2: Entertainment activities, showing that professionals used coping strategies with a focus on the problem and emotion. They pointed out the importance of social contact, spirituality, and entertainment for emotional well-being.